Rapid On-Site Detection Method for White Spot Syndrome Virus Using Recombinase Polymerase Amplification Combined With Lateral Flow Test Strip Technology - Zhang, Tianmeng; Liu, Xia; Yang, Xiaohan; Liu, Feixue; Yang, Haitao; Li, Xueqing; Feng, Huimiao; Wu, Xinyu; Jiang, Ge; Shen, Hui; Dong, Jingquan (Frontiers in Cellular and Infection Microbiology, 2022)
The white spot syndrome virus is the most destructive virus threatening the shrimp industry worldwide, causing hundreds of millions of dollars in economic losses each year. There is currently no specific medicine to treat it. Therefore, rapid and accurate detection of WSSV is of great significance for controlling its spread and reducing economic losses. Traditional detection methods, such as polymerase chain reaction (PCR) and quantitative fluorescent PCR, rely on laboratory equipment and are not suitable for field testing. In this study, recombinase polymerase amplification (RPA) combined with a lateral flow strip (LFS) was developed. This method targets the entire genome and designs primers and probes accordingly. The detection can be completed in 30 min at 37°C, and the detection limit of each reaction is 20 copies, which is much more sensitive than other detection methods. The RPA-LFS method is highly specific to the white spot syndrome virus and has no cross-reactivity with other common shrimp viruses or pathogens. In total, 100 field samples were tested and compared to the real-time PCR method. Both methods detected 8 positive results, and the positive detection rate was 100%. The method was fast, simple, specific, and sensitive. It does not rely on laboratory equipment and has broad application prospects for in-field detection, especially in remote areas with underdeveloped medical equipment.